Factorial Validity and Reliability of the Chemotherapy Dietary Adherence Scale: A Tool for Nutritional Assessment in Cancer Care - Prakash G, Hari; Kumar D, Sunil; PK, Kiran; Arun, Vanishri; Yadav, Deepika; M, Shwethashree; Gopi, Arun; Kulkarni, Praveen (Asian Pacific Journal of Cancer Care, 2025)
Background: Nutritional adherence is vital in improving clinical outcomes for chemotherapy patients. The lack of validated tools to assess dietary adherence during chemotherapy prompted the development and psychometric validation of the Chemotherapy Dietary Adherence Scale (CDAS). Objective: To develop, refine, and validate the CDAS, assessing its reliability and factorial structure through exploratory and confirmatory factor analyses. Methods: This two-phase, cross-sectional study was conducted in the Department of Medical Oncology at a tertiary care cancer centre. Data were collected from 245 chemotherapy patients over a period of two months. Phase 1 involved exploratory factor analysis (EFA) on an initial scale, followed by refinement to address weak inter-item correlations. Phase 2 validated the revised scale using confirmatory factor analysis (CFA). Reliability was assessed using Cronbach’s alpha, and statistical analysis was conducted using SPSS version 26 and Python’s semopy library. Results: The study population had a mean age of 58.13 years (SD, 9.85) and consisted predominantly of skilled workers (67.1%). The 7-item CDAS demonstrated excellent internal consistency (Cronbach’s alpha = 0.83), with subscales showing strong reliability: Nutritional Adherence (α = 0.79) and Dietary Adjustment (α = 0.81). EFA revealed a two-factor structure explaining 70.5% of the total variance. CFA confirmed this structure with exceptional model fit (χ² = 12.09, df = 13, p = 0.52; CFI = 1.00; GFI = 0.98; TLI = 1.00; RMSEA = 0.00). All items showed significant factor loadings (p < 0.001), with values ranging from 1.058 to 1.262. The moderate correlation between factors (r = 0.168, p < 0.001) indicated that they represented distinct but related dimensions of dietary adherence. Conclusions: The CDAS demonstrated robust psychometric properties, with a clear two-factor structure that captures distinct aspects of dietary adherence among chemotherapy patients. The validated scale provides a reliable and valid tool for assessing nutritional adherence and dietary adaptations during chemotherapy, potentially enhancing clinical assessment and targeted nutritional interventions.